Linguistics features of commercial emails and personal emails - Lee, Yan Neo (Universiti Malaysia Sarawak, (UNIMAS), 2002)
This project sought to gain insights into the linguistic features of email communication, the differences of text features between commercial and personal emails and the how and why people write email messages the way they do. The commercial emails are contributed by an advertising company, Celcius Design Sdn. Bhd. while the personal emails are contributed by eleven undergraduate students from various universities in Malaysia. A total of thirty emails each has been collected for the purpose of this study. Both corpuses of emails are analyzed based on a framework suggested by Li Lan (2000) in her paper entitled, Email: a challenge to Standard English?". The framework is adapted and divided into three categories; Subjects, salutations and closings, Conversational features of emails and Innovations and distinctive usages. From the findings in this study, it is found that the corpus of commercial emails show some conventions of written memos with some instances that includes choices of words and phrases that represent spoken language. As for the corpus of personal emails, it is found that most of the emails show conventions of the written letter or telephone conversation. The style and choice of words and phrases in email communication depends on the purpose of the message and the social interaction between the writer and the reader.